Community-based sampling methods for surveillance of the Chagas disease vector, Triatoma dimidiata (Hemiptera: Reduviidae: Triatominae). (2014)
In Guatemala, the most widespread vector of Trypanosoma cruzi (Kinetoplastida: Trypanosomatidae), the causative agent of Chagas disease, is Triatoma dimidiata (Latreille) (Hemiptera: Reduviidae: Triatominae). T. dimidiata is native to Guatemala and is present in both domestic and sylvatic habitats. Consequently, control of T. dimidiata is difficult because after successful elimination from homes, individual insects can recolonize homes from the surrounding environment. Therefore, intensive long-term surveillance of this species is essential to ensure adequate control is achieved. Manual inspection for signs of infestation, the current method used to monitor Triatominae throughout Central and South America, is labor and time-consuming, so cost-effective alternatives are needed. The current study compared the effectiveness of the current method of surveillance of T. dimidiata with community-based techniques of G6mez-Nuñez sensor boxes, collection and observation of bugs by householders, and presence of triatomine-like feces on walls. Although manual inspection was the most sensitive method when used alone, collection by householders also was sensitive and specific and involved less effort. Sensor boxes were not sensitive indicators of T. dimidiata infestation when used alone. Two recorded variables, visual inspection for feces and the sighting of bugs by householders, were sensitive and specific indicators of infestation, and in combination with collection by householders and sensor boxes these methods were significantly more likely to detect infestations than manual inspection alone. A surveillance program that combines multiple community-based techniques should have low cost and involve minimal effort from the government and at the same time promote sustainable community involvement in disease prevention.